A degradable medicinal plastic bottle and preparation method thereof
By mixing raw materials such as polylactic acid, biodegradable elastomer and preparing through twin-screw extruder and blow molding process, the problem of difficult degradation of existing pharmaceutical plastic bottles is solved, and high mechanical properties and degradability are achieved environmentally friendly effect.
Patent Information
- Application Number
- CN202411817725.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Existing pharmaceutical plastic bottles are mainly made of non-degradable materials, which are difficult to degrade naturally, resulting in environmental pollution. The existing degradable materials have defects in mechanical properties and cannot be applied to pharmaceutical plastic bottles.
Degradable pharmaceutical plastic bottles are prepared through twin-screw extruders and blow molding processes using raw materials such as polylactic acid, biodegradable elastomers, compound plasticizers, nucleating agents and modified titanium dioxide.
The mechanical properties and crystallization properties of polylactic acid are improved, the mechanical properties and impact resistance of plastic bottles are enhanced, and the photocatalytic efficiency and antibacterial properties are improved by loading Ag3PO4, and the photocatalytic efficiency and antibacterial properties are achieved, achieving degradable environmental protection effects.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic materials, in particular to a degradable medicinal plastic bottle and a preparation method thereof. Background Art
[0002] In the pharmaceutical packaging sector, plastic bottles are widely used due to their lightweight, durable, and easy-to-process and transport properties. With the increasing global awareness of environmental protection, the use of biodegradable materials has become a key trend in the packaging industry. However, existing pharmaceutical plastic bottles often fail to adapt to this trend and still rely heavily on non-biodegradable materials. This not only limits their environmental performance but also hinders their competitiveness in the future market.
[0003] Chinese invention patent CN111216338B details a method for processing pharmaceutical plastic bottles. This method not only focuses on production efficiency and cost control, but also enhances the applicability and flexibility of plastic bottles through technological innovation. However, despite the important role pharmaceutical plastic bottles play in protecting drugs from external environmental interference, ensuring drug stability, and extending drug shelf life, existing pharmaceutical plastic bottles still have some significant problems. For example, traditional pharmaceutical plastic bottles are mainly made of non-degradable materials such as polyethylene (PE), polypropylene (PP), or PET. These plastic bottles are difficult to decompose naturally after being discarded, causing long-term environmental pollution. Existing degradable materials have mechanical property defects, which make them unsuitable for use in pharmaceutical plastic bottles. Summary of the Invention
[0004] (1) Technical problems solved
[0005] In view of the deficiencies of the prior art, the present invention provides a degradable medicinal plastic bottle and a preparation method thereof, which solves the problem that the existing medicinal plastic bottles are difficult to degrade.
[0006] (2) Technical solution
[0007] To achieve the above objectives, in a first aspect, the present application provides a degradable medicinal plastic bottle and a preparation method thereof, which adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a degradable medicinal plastic bottle, the raw material components including polylactic acid, a biodegradable elastomer, a compound plasticizer, a nucleating agent, and a photosensitizer, wherein the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, and photosensitizer is 100: (15-20): (2-4): (2-4): (1-3);
[0009] The biodegradable elastomer is obtained by mixing polyhydroxybutyrate, polycaprolactone, and polybutylene succinate in equal weight ratios; the compound plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate; the nucleating agent is one of polylactic acid stereocomplex and TMC-200; and the photosensitizer is modified titanium dioxide.
[0010] The raw material components are mixed evenly and then added into a twin-screw extruder, and a degradable medicinal plastic bottle is prepared through melt blending and blow molding.
[0011] Preferably, the polylactic acid is a mixture of poly L-lactic acid and poly D-lactic acid, and the polylactic acid has a glass transition temperature of 60°C, a melting point of 180°C, a tensile strength of 50-65 MPa, an elastic modulus of 2000-3500 MPa, an elongation of 6%-10%, and a relative density of 1.24 g / cm 3 .
[0012] Preferably, the polylactic acid has a glass transition temperature of 60°C, a melting point of 180°C, a tensile strength of 50-65 MPa, an elastic modulus of 2000-3500 MPa, a flexural strength of about 100 MPa, a flexural modulus of 3000-4000 MPa, and a relative density of 1.24 g / cm 3
[0013] Preferably, the modified titanium dioxide is obtained by:
[0014] Step S11, weighing a certain amount of loose dried kapok, and soaking it in an absolute ethanol solution of TBOT at room temperature, leaving it to stand for 24 hours, then taking it out and placing it in the air for hydrolysis for 2 hours;
[0015] Step S12: After the hydrolysis is completed, the kapok is placed in a drying furnace and dried and calcined at 50° C., and the tubular TiO2 is collected for later use;
[0016] Step S13: Under magnetic stirring, 0.1 g of AgNO3 was added to 50 mL of an aqueous solution containing 0.5 g of PVP. After stirring for 30 min, 200 mg of tubular TiO2 was dispersed in the solution. After stirring for another 30 min, 5 mL of 0.1 mol of NaHPO4 was slowly added dropwise to the solution. After ultrasonic stirring, the solution was allowed to stand for 4 h.
[0017] Step S14: collecting the precipitate by centrifugation, washing it twice with deionized water and anhydrous ethanol, and then placing the sample in a drying oven and drying it at 50° C. for 6 h to obtain a 1:2 Ag 3 PO 4 / TiO 2 composite material;
[0018] Step S15, surface modification of the collected Ag3PO4 / TiO2 composite material is performed using a silane coupling agent to improve the stability of the Ag3PO4 / TiO2 composite material and to improve its light absorption performance and photocatalytic activity;
[0019] Step S16: Dry in a drying oven at 60°C for 24 hours. In order to improve the crystallinity of the Ag3PO4 / TiO2 composite material nanoparticles, anneal the Ag3PO4 / TiO2 composite material in a muffle furnace at 350°C for 2 hours to obtain modified titanium dioxide.
[0020] The explanation shows that the combination of Ag3PO4 and titanium dioxide can effectively improve the light absorption performance of plastic bottles and accelerate the degradation rate; after ultrasonic stirring, the tubular titanium dioxide breaks into tile-like flakes, and still has a large surface area after mixing with Ag3PO4; when the Ag3PO4 content is too much, the degradation rate slows down because it covers the active points of titanium dioxide. After mixing with other raw materials, Ag3PO4 particles act as "fillers" to increase the density and hardness of the plastic, improve impact resistance and wear resistance, and at the same time form physical cross-linking points through interaction with plastic molecular chains, further enhancing mechanical properties and hardness.
[0021] Preferably, the compound plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate in a ratio of 2:2:1:1, based on mass fraction.
[0022] Preferably, the bio-based polycarboxylic acid plasticizer is obtained by using glycerol and succinic anhydride derived from biomass as raw materials, synthesizing bio-based polycarboxylic acid through esterification reaction, and then performing a ring-opening reaction with hydrophobic epoxy soybean oil. By controlling different carboxyl / epoxy equivalent ratios (R=0.4), a high-molecular-weight bio-based polycarboxylic acid plasticizer containing flexible long carbon chains is prepared. The bio-based polycarboxylic acid plasticizer is degradable and has good compatibility with PLA.
[0023] Preferably, the hydrophobic epoxidized soybean oil is obtained by removing the hydrophilic components by solvent extraction using the difference in solubility of hydrophobic alcohol solvents for different polar components in the epoxidized soybean oil to obtain the hydrophobic epoxidized soybean oil; the hydrophobic alcohol solvent is one of tert-butanol, isobutanol, n-pentanol, sec-pentanol and n-hexanol.
[0024] Preferably, the cellulose grafted polycaprolactone derivative is obtained by adding microcrystalline cellulose, dimethyl sulfoxide and an organic base DBU (1,8-diazabicycloundec-7-ene) into a high-pressure reactor, replacing with CO2, and reacting for a certain period of time under a stable state to obtain a clear and transparent cellulose homogeneous solution, using the organic base DBU as an organic catalyst to make the cellulose hydroxyl group as an initiator and polymerize with the Ɛ-caprolactone ring-opening reaction, thereby synthesizing the cellulose grafted polycaprolactone derivative.
[0025] Preferably, the modified castor oil is obtained by first conducting an esterification reaction between sebacic acid and castor oil in a flask, with the main ratio of carboxyl groups to hydroxyl groups being 1:1.5, to obtain the modified castor oil.
[0026] Preferably, the degradation rate is controlled by setting a photosensitizer gradient or surface contact area in the raw material components; the body of the degradable pharmaceutical plastic bottle gradually turns brown as it is exposed to light, because silver nitrate turns brown under ultraviolet light or sunlight;
[0027] It is explained that by designing the first layer of the surface into a microporous structure, the contact area between the photosensitizer and light is increased; by increasing the amount of photosensitizer used, the degradation rate is increased.
[0028] In a second aspect, the present invention provides a method for preparing a degradable medicinal plastic bottle, comprising the following steps:
[0029] Step 1, weighing the raw material components according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, and photosensitizer of 100: (15-20): (2-4): (2-4): (1-3);
[0030] Step 2: using a high-speed mixer to fully mix the raw material components to obtain a resin mixture;
[0031] Step 3: Melting the resin mixture at 100-400° C. and extruding to obtain a composite resin material;
[0032] Step 4: Blow-molding the combined resin material at 190-215° C. to obtain a degradable medicinal plastic bottle.
[0033] (3) Beneficial effects
[0034] The present invention provides a degradable medicinal plastic bottle and a preparation method thereof, which have the following beneficial effects:
[0035] (1) The degradable medicinal plastic bottle provided by the present invention is prepared by mixing a biodegradable elastomer, a compound plasticizer, a nucleating agent, a photosensitizer and polylactic acid, adding the mixture to a twin-screw extruder, and extruding and granulating the mixture after melt blending to obtain a modified polylactic acid degradable composite material, which enhances the mechanical properties and crystallization properties of polylactic acid, reduces water vapor permeability, and improves the toughness of polylactic acid; by loading Ag3PO4 on titanium dioxide, the spectral response range of the modified polylactic acid degradable composite material is broadened, the light absorption capacity is improved, the recombination probability of electron-hole pairs is reduced, and the photocatalytic efficiency is improved; at the same time, Ag3PO4 is a substance with antibacterial properties, and its application in medicinal plastic bottles can reduce the growth and reproduction of bacteria, thereby keeping the medicines clean and hygienic, and effectively solving the problem of insufficient physical properties, photocatalytic efficiency and antibacterial properties of plastic bottles in the prior art.
[0036] (2) The biodegradable medicinal plastic bottle provided by the present invention controls the degradation rate by setting the photosensitizer gradient or surface contact area in the raw material components; as the body of the biodegradable medicinal plastic bottle is exposed to light, it gradually turns brown, which helps to control the degradation rate of the plastic bottle and indicates the degradation rate of the plastic bottle.
[0037] (3) The biodegradable pharmaceutical plastic bottle provided by the present invention is compounded with plasticizers to improve tensile properties, flexibility, and fracture strength. The bio-based polycarboxylic acid plasticizer lowers the glass transition temperature of polylactic acid, the cellulose-grafted polycaprolactone derivative enhances the compatibility of polylactic acid, and the modified castor oil improves the flexibility and impact resistance of polylactic acid. These components work together to significantly improve the flexibility and various mechanical properties of polylactic acid. DETAILED DESCRIPTION
[0038] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0039] Preparation Examples A1-A4 are used to prepare a biodegradable elastomer, a compounded plasticizer, a nucleating agent, and a photosensitizer, including:
[0040] Preparation Example A1: The biodegradable elastomer is obtained by mixing polyhydroxybutyrate, polycaprolactone, and polybutylene succinate in equal weight proportions.
[0041] Preparation Example A2: The composite plasticizer is prepared by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate in a ratio of 2:2:1:1.
[0042] The bio-based polycarboxylic acid plasticizer is obtained by using glycerol and succinic anhydride derived from biomass as raw materials, synthesizing bio-based polycarboxylic acids through an esterification reaction, and then undergoing a ring-opening reaction with hydrophobic epoxy soybean oil. By controlling different carboxyl / epoxy equivalent ratios (R=0.4), a high-molecular-weight bio-based polycarboxylic acid plasticizer containing flexible long carbon chains is prepared. The bio-based polycarboxylic acid plasticizer is biodegradable and has good compatibility with PLA. The hydrophobic epoxy soybean oil is obtained by removing the hydrophilic components in the epoxy soybean oil by solvent extraction using the different solubility of hydrophobic alcohol solvents for different polar components. The hydrophobic alcohol solvent is one of tert-butyl alcohol, isobutyl alcohol, n-pentanol, sec-pentanol, and n-hexanol.
[0043] The cellulose grafted polycaprolactone derivative is obtained by adding microcrystalline cellulose, dimethyl sulfoxide and an organic base DBU into a high-pressure reactor, replacing the mixture with CO2, and reacting the mixture for a certain period of time under a stable state to obtain a clear and transparent cellulose homogeneous solution. The organic base DBU is used as an organic catalyst to cause the cellulose hydroxyl group as an initiator to react with Ɛ-caprolactone to undergo a ring-opening polymerization reaction, thereby synthesizing the cellulose grafted polycaprolactone derivative.
[0044] The modified castor oil is obtained by: firstly performing an esterification reaction between sebacic acid and castor oil in a flask, with the main ratio of carboxyl group to hydroxyl group being 1:1.5, to obtain the modified castor oil.
[0045] Preparation Example A3, the nucleating agent is one of a polylactic acid stereocomplex and TMC-200, wherein the process of obtaining the polylactic acid stereocomplex includes the following steps: melting left-handed polylactic acid, right-handed polylactic acid and polyethylene glycol at 200°C, and processing through a twin-screw extruder or an internal mixer to obtain a polylactic acid stereocomplex.
[0046] Preparation Example A4: The photosensitizer is modified titanium dioxide, and the process for obtaining the modified titanium dioxide includes the following steps:
[0047] Step S11, weighing a certain amount of loose dried kapok, and soaking it in an absolute ethanol solution of TBOT at room temperature, leaving it to stand for 24 hours, then taking it out and placing it in the air for hydrolysis for 2 hours;
[0048] Step S12: After the hydrolysis is completed, the kapok is placed in a drying furnace and dried and calcined at 50° C., and the tubular TiO2 is collected for later use;
[0049] Step S13: Under magnetic stirring, 0.1 g of AgNO3 was added to 50 mL of an aqueous solution containing 0.5 g of PVP. After stirring for 30 min, 200 mg of tubular TiO2 was dispersed in the solution. After stirring for another 30 min, 5 mL of 0.1 mol of NaHPO4 was slowly added dropwise to the solution. After ultrasonic stirring, the solution was allowed to stand for 4 h.
[0050] Step S14: collecting the precipitate by centrifugation, washing it twice with deionized water and anhydrous ethanol, and then placing the sample in a drying oven and drying it at 50° C. for 6 h to obtain a 1:2 Ag 3 PO 4 / TiO 2 composite material;
[0051] Step S15, surface modification of the collected Ag3PO4 / TiO2 composite material is performed using a silane coupling agent to improve the stability of the Ag3PO4 / TiO2 composite material and to improve its light absorption performance and photocatalytic activity;
[0052] Step S16: Dry in a drying oven at 60°C for 24 hours. In order to improve the crystallinity of the Ag3PO4 / TiO2 composite material nanoparticles, anneal the Ag3PO4 / TiO2 composite material in a muffle furnace at 350°C for 2 hours to obtain modified titanium dioxide.
[0053] Preparation Examples B1-B7 are used to prepare degradable pharmaceutical plastic bottles;
[0054] Preparation Example B1: Test product 1 was obtained by the following preparation process; the preparation process of the degradable medicinal plastic bottle includes the following steps:
[0055] Step 1, weighing raw material components according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, and photosensitizer of 100:15:2:2:2;
[0056] Step 2: using a high-speed mixer to fully mix the raw material components to obtain a resin mixture;
[0057] Step 3: Melting the resin mixture at 225° C. and extruding to obtain a composite resin material;
[0058] Step 4: Blow-molding the combined resin material at 190-215° C. to obtain a degradable medicinal plastic bottle.
[0059] It needs to be further explained that the polylactic acid is a mixture of poly L-lactic acid and poly D-lactic acid, and the polylactic acid has a glass transition temperature of 60°C, a melting point of 180°C, a tensile strength of 50-65 MPa, an elastic modulus of 2000-3500 MPa, an elongation of 6%-10%, and a relative density of 1.24 g / cm 3 .
[0060] It needs to be further explained that in Preparation Example B1, the biodegradable elastomer is obtained by mixing polyhydroxybutyrate, polycaprolactone, polybutylene succinate and other ingredients in a weight ratio; the compound plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate in a ratio of 2:2:1:1; the nucleating agent is TMC-200; and the photosensitizer is modified titanium dioxide.
[0061] Preparation Example B2: Test product 2 was obtained by the following preparation process; the preparation process of the degradable medicinal plastic bottle includes the following steps:
[0062] Step 1, weighing raw material components according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, and photosensitizer of 100:18:3:2:2;
[0063] Step 2: using a high-speed mixer to fully mix the raw material components to obtain a resin mixture;
[0064] Step 3: Melting the resin mixture at 225° C. and extruding to obtain a composite resin material;
[0065] Step 4: Blow-molding the combined resin material at 190-215° C. to obtain a degradable medicinal plastic bottle.
[0066] It needs to be further explained that in Preparation Example B1, the biodegradable elastomer is obtained by mixing polyhydroxybutyrate, polycaprolactone, polybutylene succinate and other ingredients in a weight ratio; the compound plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate in a ratio of 2:2:1:1; the nucleating agent is a polylactic acid stereocomplex; and the photosensitizer is modified titanium dioxide.
[0067] Preparation Example B3: Test product 3 was obtained by the following preparation process; the preparation process of the degradable medicinal plastic bottle includes the following steps:
[0068] Step 1, weighing raw material components according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, and photosensitizer of 100:20:2:4:1;
[0069] Step 2: using a high-speed mixer to fully mix the raw material components to obtain a resin mixture;
[0070] Step 3: Melting the resin mixture at 225° C. and extruding to obtain a composite resin material;
[0071] Step 4: Blow-molding the combined resin material at 190-215° C. to obtain a degradable medicinal plastic bottle.
[0072] It needs to be further explained that in Preparation Example B3, the biodegradable elastomer is obtained by mixing polyhydroxybutyrate, polycaprolactone, polybutylene succinate, etc. in a weight ratio; the compound plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose-grafted polycaprolactone derivative, modified castor oil, and acetyl tributyl citrate in a ratio of 2:2:1:1; the nucleating agent is TMC-200; and the photosensitizer is modified titanium dioxide.
[0073] Preparation Example B4, Test Product 4 was obtained by the following preparation process; the difference from Preparation Example B3 is that the raw material components are weighed according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, and photosensitizer of 100:20:2:4:2.
[0074] Preparation Example B5, Test Product 5 was obtained by the following preparation process; the difference from Preparation Example B3 is that the raw material components were weighed according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, and photosensitizer of 100:20:2:4:3.
[0075] Preparation Example B6: Sample 6 was obtained by the following preparation process; the difference from Preparation Example B1 is that:
[0076] The raw material components were weighed according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer of 100:18:2:2:1.
[0077] Preparation Example B7, Test Product 7 was obtained by the following preparation process; the difference from Preparation Example B1 is that,
[0078] The raw material components were weighed according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer of 100:20:3:4:2.
[0079] Test case, used to analyze the mechanical properties, degradation properties and water vapor transmission rate of test products 1-7 and control groups 1-3;
[0080] The difference between control group 1 and test sample 1 is that the plasticizer is different; the preparation method of control group 1 is: polylactic acid, biodegradable elastomer, plasticizer, nucleating agent, and photosensitizer are blended in a ratio of 100:15:2:2:2; the raw material components are mixed evenly and then added to a twin-screw extruder, and the melt blending and blow molding are performed to prepare control group 1;
[0081] Furthermore, the plasticizer is epoxidized soybean oil;
[0082] The difference between control group 2 and test sample 1 is that the photosensitizer is different; the preparation method of control group 2 is: polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, and photosensitizer are blended in a ratio of 100:15:2:2:2; the raw material components are mixed uniformly and then added to a twin-screw extruder, and control group 2 is prepared by melt blending and blow molding;
[0083] Furthermore, the photosensitizer is titanium dioxide nanoparticles;
[0084] Control group 3 is a polylactic acid degradable plastic bottle, which is prepared by obtaining a polylactic acid raw material through a lactide ring-opening polymerization method, heating the polylactic acid raw material to a molten state, and blowing the molten polylactic acid through a mold into a plastic bottle with a specific shape.
[0085] Test method
[0086] Mechanical properties test: A universal testing machine was used to perform mechanical properties tests to evaluate the mechanical properties and stability of the samples. The tensile modulus, tensile strength, flexural modulus, and flexural strength were obtained by averaging multiple measurements. The mechanical properties parameters are shown in Table 1. It was found that samples 1-7 had better mechanical properties than control group 3.
[0087] Weathering test: Test samples 1-7 and control groups 1-3 were placed in a UV-visible light aging test chamber, and the samples were taken out regularly to measure changes in appearance, color, and hardness. The hardness loss rates of test samples 1-7 after 15 days of UV irradiation at an intensity of 3000uW / cm were 8.9%, 9.1%, 9.5%, 10.3%, 11.8%, 9.4%, and 10.1%, respectively. The degradation rate of test samples 3-5 increased, and the color of the test samples changed as the degradation progressed. The hardness loss rates of control groups 1-3 were 9.6%, 7.2%, and 10.7%, respectively.
[0088] Water vapor transmission rate test: The test was conducted at a temperature of 25°C ± 2°C and a relative humidity of 95% ± 5%. The water vapor transmission rates of samples 1-7 were 37.5 mg / (24h·L), 43.0 mg / (24h·L), 43.8 mg / (24h·L), 43.4 mg / (24h·L), 43.4 mg / (24h·L), 49.5 mg / (24h·L), and 53.3 mg / (24h·L), respectively, with an average water vapor transmission rate of 43.4 mg / (24h·L).
[0089] Table 1 Mechanical properties parameters
[0090]
[0091] Summary: The biodegradable pharmaceutical plastic bottle provided by the present invention has excellent mechanical properties, moderate degradation performance, good water vapor barrier properties and environmental friendliness, which makes this material have broad application prospects and market potential in the field of pharmaceutical packaging.
[0092] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A degradable medical plastic bottle, the raw material components include polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent, photosensitizer, characterized in that: The mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer is 100: (15-20): (2-4): (2-4): (1-3); The biodegradable elastomer is obtained by mixing polyhydroxybutyrate, polycaprolactone, polybutylene succinate in equal weight ratios; According to the mass fraction, the composite plasticizer is obtained by mixing a bio-based polycarboxylic acid plasticizer, a cellulose grafted polycaprolactone derivative, a modified castor oil, and acetyl tributyl citrate in a ratio of 2:2:1:1; the bio-based polycarboxylic acid plasticizer is obtained by using glycerol and succinic anhydride derived from biomass as raw materials, synthesizing a bio-based polycarboxylic acid through an esterification reaction, and then performing a ring-opening reaction with hydrophobic epoxy soybean oil, and controlling the equivalent ratio of different carboxyl groups to epoxy groups to be 0.4, and preparing a high molecular weight bio-based polycarboxylic acid plasticizer containing a flexible long carbon chain through the reaction, wherein the bio-based polycarboxylic acid plasticizer is degradable and has good compatibility with PLA; the hydrophobic epoxy soybean oil is obtained by using a hydrophobic alcohol solvent to react the different polar components in the epoxy soybean oil. The hydrophilic component is removed by solvent extraction to obtain hydrophobic epoxy soybean oil; the hydrophobic alcohol solvent is one of tert-butyl alcohol, isobutyl alcohol, n-pentanol, sec-pentanol and n-hexanol; the cellulose grafted polycaprolactone derivative is obtained by adding microcrystalline cellulose, dimethyl sulfoxide and organic base DBU into a high-pressure reactor, replacing with CO2, reacting for a certain period of time under a stable state to obtain a clear and transparent cellulose homogeneous solution, using organic base DBU as an organic catalyst to make cellulose hydroxyl as an initiator and Ɛ-caprolactone ring-opening reaction polymerization, thereby synthesizing cellulose grafted polycaprolactone derivatives; the modified castor oil is obtained by esterification reaction of sebacic acid and castor oil in a flask, and the ratio of carboxyl to hydroxyl is 1:1.5 to obtain modified castor oil; The nucleating agent is TMC-200; the photosensitizer is modified titanium dioxide; The modified titanium dioxide is obtained by: Step S11, weigh a certain amount of loose dry kapok, and soak it in an absolute ethanol solution of TBOT at room temperature, let it stand for 24 hours, then take it out and put it in the air for hydrolysis for 2 hours; Step S12: After the hydrolysis is completed, the kapok is placed in a drying furnace and dried and calcined at 50° C., and the tubular TiO2 is collected for later use; Step S13, under magnetic stirring, add 0.1 g of AgNO3 to 50 mL of an aqueous solution containing 0.5 g of PVP, stir for 30 min, disperse 200 mg of tubular TiO2 in the solution, stir again for 30 min, slowly drop 5 mL of 0.1 mol NaHPO4 into the solution, and let stand for 4 h after ultrasonic stirring; Step S14, collecting the precipitate by centrifugation, washing twice with deionized water and anhydrous ethanol, and then placing the sample in a drying oven and drying it at 50° C. for 6 h to obtain a 1:2 Ag3PO4 / TiO2 composite material; Step S15, surface modification of the collected Ag3PO4 / TiO2 composite material is performed by using a silane coupling agent to improve the stability of the Ag3PO4 / TiO2 composite material and improve its light absorption performance and photocatalytic activity; Step S16, drying in a drying oven at 60° C. for 24 h, and annealing the Ag3PO4 / TiO2 composite material in a muffle furnace at 350° C. for 2 h to obtain modified titanium dioxide in order to improve the crystallinity of the Ag3PO4 / TiO2 composite material nanoparticles; The raw material components are mixed evenly and then added into a twin-screw extruder, and a degradable medicinal plastic bottle is prepared through melt blending and blow molding.
2. A degradable medicinal plastic bottle according to claim 1, characterized in that: The average water vapor permeability of biodegradable plastic bottles is 43.4 mg / (24h·L).
3. A degradable medicinal plastic bottle according to claim 1, characterized in that: The degradation rate can be controlled by setting the photosensitizer gradient in the raw material components or the surface contact area.
4. A method for preparing a degradable medicinal plastic bottle according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, weigh the raw material components according to the mass ratio of polylactic acid, biodegradable elastomer, compound plasticizer, nucleating agent and photosensitizer of 100: (15-20): (2-4): (2-4): (1-3); Step 2: using a high-speed mixer to fully mix the raw material components to obtain a resin mixture; Step 3, melting the resin mixture at 225° C. and extruding to obtain a composite resin material; Step 4: Blow-molding the combined resin material at 190-215° C. to obtain a degradable medicinal plastic bottle.
Citation Information
Patent Citations
A method for processing pharmaceutical plastic bottles
CN111216338B
Low-cost degradable plastic bottle and preparation method thereof
CN116041923A
Degradable plastic medicine bottle and preparation method thereof
CN118791852A